Mobile Genetic Elements Contributing to Carbapenem Resistance in Acinetobacter baumannii: Current Insights - Mardhiyah, Azzahrah Khairunnisa; Saharman, Yulia Rosa; Sjatha, Fithriyah (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Acinetobacter baumannii has become a major cause of hospital-acquired infections with the rapid development of resistance to multiple antibiotics, including critical carbapenems. This resistance challenge limits treatment options and increases morbidity and mortality. The genetic plasticity of A. baumannii facilitates the mobilization of resistance genes via mobile genetic elements (MGE). Addressing this crisis requires a deeper understanding of the mechanisms by which MGE propagates carbapenem resistance. This paper provides a solution by systematically reviewing recent research on the role of MGE in disseminating resistance genes. Following PRISMA guidelines, a comprehensive literature review was conducted across various databases. The review revealed that resistance mechanisms primarily involve carbapenem-hydrolyzing enzymes and MGE, such as integrons, transposons, insertion sequences, and plasmids. Notably, genes like blaOXA-23 and blaNDM are frequently mobilized by these elements, facilitating horizontal gene transfer and persistence. Understanding the mechanisms of MGE-mediated gene transfer is crucial for developing strategies to control the spread of antibiotic resistance inÂ A. baumannii.